The Structure, Problems and Solutions of Fruit Sapling Producing Enterprises in Hatay Province - Nuran Tapkı; Faruk Emeksiz; Erdal Dağıstan (Turkish Journal of Agriculture: Food Science and Technology)
In this study, examined the structure and problems of fruit sapling producing enterprises and offers solutions in The Hatay Province. The data were obtained from 92 enterprises by the method of full count and face to face with producers. Of the 51.15% population in creating family business primary school graduates, the proportion of university graduates remained at 8.62%. The rate of agricultural engineer employment in the businesses is 2.18%. While 64.05% of the enterprisers the father's profession, this profession began taking 3.37's% of nursery education. Average potential family labour is the 4.22 male labour forces in enterprises. The family labour utilization rate was calculated as 50.71%. Of the 88.48% in fruit sapling businesses, 5.32's% in other agricultural productions and 5.22's% in non-agricultural jobs of total used men workforce. The businesses have average total land size of 25.74 acres which it has established 12 acres of fruit sapling production land. While 74.58% of the total fruit sapling land is property, 25.42's% is for rent situation. The operating capital is calculated as the average of 229.308 TL. The most common species of fruit sapling production were citrus (46.20%) and olive trees (35.29%). The problems faced by most of the farms in the region were high input prices, excessive bureaucratic procedures preventing memberships into the union, an inadequate amount of support provided by the state, production-threatening diseases of plants and difficulties in finding qualified staff in the region. The results show that enterprises need to increase their production capacity, to unite under one organization to facilitate the resolution of problems.